The Integration Perspectives for Historical Study of Indonesian Islam - Abdurahman, Dudung (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: During 15 centuries, Islam has always met with many cultures, even Moslems who come from different ethnic and social backgrounds have made Islam a multicultural reality. Therefore, the paradigm of humanity science will be always actual to understand the reality of Islamic society in the context of the integration amongs historical religious and cultural perspectives. The three perspectives can become on epistemology of